Implementasi Peaceful End of Life Berbasis Nilai Budaya Mandar di Ruang ICU RSUD Majene - Helmi Juwita Helmi; Nurwahita Nurwahita; Muhammad Qasim; Lulu Nur Intang; Wanda Apriliani Klara; Rusmini Rusmini (Jurnal Ners, 2026)
The implementation of a peaceful end of life is one of the implementations that aims to improve the quality of life of patients with severe illnesses and provide a peaceful end of life, and is very important for patients with end-of-life care in the ICU by paying attention to the patient's culture. This study aims to explore the experiences of nurses in implementing a peaceful end of life based on Mandar cultural values ​​in the ICU of Majene Regional Hospital. This study used a qualitative design with a purposive sampling technique in accordance with the inclusion and exclusion criteria. The instrument used was an interview guide related to the implementation of a peaceful end of life by paying attention to aspects of Mandar cultural values ​​​​concerning pain freedom, feeling comfortable, feeling dignified, being in peace and family closeness with the closest person. The study was conducted in August 2025 with 7 informants. The results of the study showed that nurses have experience in implementing a peaceful end of life based on Mandar cultural values ​​​​concerning pain freedom, feeling comfortable, feeling dignified, being in peace, and family closeness with the closest person.